The spatial relationship between patterns of disappeared streams and residential development in Portland, Oregon, USA. Issue 2 (1st December 2022) - Post, Gregory C.; Chang, Heejun; Banis, David
ABSTRACT: Disappeared streams are streams that have been buried, removed, or moved as part of the urbanization process. We identified disappeared streams in the Portland, Oregon metropolitan area using historical topographic maps for four time periods, and related them to the history of urban development. The historical maps were used to identify streams visible in older maps but not shown in a more recent version. From 1852 to 1895, 15% of streams disappeared, but the majority of streams disappeared between 1896 and 1953 (65%). This trend continued mainly in suburban areas after 1954 with 12% of streams being removed from 1954 to 1989 and 8% from 1990 to 2017. Stream disappearance can be linked to residential development and prior conversion of land for agriculture depending on the area and time period. Mapping disappeared streams can help urban spatial planners identify where stream daylighting or restoration could be targeted.